A conjugated polymer, preparation method thereof and application in electrochromic device

By designing a conjugated polymer containing cyclodioxythiophene and a nitrogen heterocycle and introducing bridge groups and end-capped groups, the existing electrochromic materials lack black tint state and insufficient performance are solved, and an efficient and stable black electrochromic effect is achieved.

CN119192546BActive Publication Date: 2025-04-04YANTAI ZHENGHAI HIGH TECH +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411720082.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-04-04
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

Existing electrochromic materials have problems such as short cycle life, poor chemical stability, complicated synthesis steps and slow response time. In particular, there is a lack of materials that can achieve black tinting, which limits the further application of electrochromic technology and market expansion.

Method used

A conjugated polymer is adopted, with a structure of cyclodioxythiophene as an electron donor and a nitrogen heterocycle as an electron acceptor, and the chain spacing and charge transfer are adjusted through bridge groups, combining end capping groups to improve chemical stability, achieving black chromic state and excellent electrochromic properties.

Benefits of technology

It realizes black tinting state, significantly improves the cycle life and chemical stability of the material, reduces the turn-on voltage and response time, and is suitable for the research and development of high-performance electrochromic materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192546B_ABST
    Figure CN119192546B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of polymer optoelectronic materials, and in particular, relates to a conjugated polymer, a preparation method thereof, and an application in an electrochromic device. Compared with the prior art, the present invention provides a conjugated polymer with cyclodioxythiophene as a core functional group, which has a "donor-bridging group-acceptor" chain structure, not only achieving a black coloring state, but also having a shorter response time, a lower turn-on voltage, and a higher cycle life. The polymer optimizes the absorption spectrum by adjusting the distance between the donor and the acceptor, and adds a stable end-capping group to improve the chemical stability, which is of great significance to the research and development of high-performance electrochromic materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer optoelectronic materials, and in particular relates to a conjugated polymer, a preparation method thereof and an application thereof in an electrochromic device. Background Art

[0002] Electrochromism is a phenomenon in which a material undergoes an electrochemical redox reaction under electrical stimulation, resulting in a reversible change in the absorption spectrum. In 1969, Deb first reported the electrochromic properties of amorphous tungsten trioxide, marking the birth of electrochromic materials. In 1984, Lampert and Granqvist proposed the concept of smart windows based on electrochromic materials. After being stimulated by electrical signals, this product can change the transmittance of light entering the building, thereby replacing physical curtains.

[0003] At present, electrochromic technology has shown great application potential in goggles, electronic product housings, automotive anti-glare rearview mirrors, light modulators, electronic price tags and energy storage. As the latest generation of commercial electrochromic materials, conjugated polymer electrochromic materials still have common problems such as short cycle life, poor chemical stability, complicated synthesis steps and slow response time. In particular, there is a lack of materials that can achieve a black coloring state, which limits the further application and market expansion of electrochromic technology.

[0004] As a typical conjugated polymer material, polythiophene has excellent film-forming properties, electrical conductivity, easy modification, and film flexibility, and shows good chemical stability against moisture and oxygen. However, due to the poor solubility of unsubstituted polythiophene and the fact that polythiophene will decompose due to peroxidation at higher potentials, its electrochromic performance has decreased, thus limiting its early application. Currently, researchers usually choose modified thiophene monomers to prepare polythiophene derivatives to improve their cycle life, response time, and regulate the color of the colored state. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a conjugated polymer, a preparation method thereof and an application in an electrochromic device, wherein the conjugated polymer not only realizes a black coloring state but also has a shorter response time, a lower turn-on voltage and a higher cycle life.

[0006] The present invention provides a conjugated polymer, as shown in formula (I):

[0007] Formula (I);

[0008] Wherein, a1 is an integer of 1 to 15, a2 is an integer of 0 to 5, the sum of a1+a2 is an integer of 1 to 20, b is an integer of 1 to 10, c is an integer of 1 to 5; n is the degree of polymerization;

[0009] R 1-1 ~R 1-8 Each is independently selected from H, C1~C10 alkyl or C1~C10 alkoxy;

[0010] R2 is selected from H, C1~C20 alkyl or C1~C20 alkoxy;

[0011] X1 and X2 are H or C-R1′; when X1 and X2 are H, X5 and X6 are not present; when X1 and X2 are C-R1′, X5 and X6 are each independently selected from C-R2′;

[0012] X3 and X4 are H or C-R3′; when X3 and X4 are H, X7 and X8 are not present; when X3 and X4 are C-R3′, X7 and X8 are each independently selected from C-R4′;

[0013] X9 is selected from S, O or N-R5′;

[0014] X 10 With X 11 is H or C-R6′; when the X 10 With X 11 When H, X 12 With X 13 does not exist; when the X 10 With X 11 When it is C-R6′, X 12 With X 13 Each is independently selected from C-R7′;

[0015] R1′ to R7′ are each independently selected from H, C1 to C10 alkyl or C1 to C10 alkoxy;

[0016] Ar1 is selected from substituted or unsubstituted phenyl, substituted or unsubstituted condensed ring aryl;

[0017] Ar2 is selected from substituted or unsubstituted dibenzazepamycin;

[0018] The substituents in the substituted phenyl group, the substituted condensed ring aromatic group and the substituted dibenzazepine heterocyclic group are each independently selected from one or more of a C1-C20 alkyl group and a C1-C20 alkoxy group.

[0019] Preferably, the sum of a1+a2 is an integer of 10 to 20, b is an integer of 5 to 10, and c is an integer of 1 to 2;

[0020] The number average molecular weight Mn of the conjugated polymer is 3000-200000.

[0021] Preferably, the R1′ to R7′ are each independently selected from H, methyl, methoxy, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl or tert-butyl;

[0022] R 1-1 ~R 1-8 Each is independently selected from H, methyl, methoxy, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl or tert-butyl;

[0023] R2 is selected from H, methoxy, methyl, ethoxy, n-propoxy, isopropoxy, n-butoxy, sec-butoxy, tert-butoxy, isopentyloxy, 2-ethylhexyloxy, n-hexyloxy, n-heptyloxy, n-octyloxy, n-nonyloxy, n-decyloxy, n-undecyloxy, n-dodecyloxy, 2-butyloctyloxy, 2-hexyldecyloxy, 2-octyldodecyloxy or 2-decyltetradecyloxy;

[0024] The substituents in the substituted phenyl group, the substituted condensed ring aromatic group and the substituted dibenzazepine heterocyclic group are each independently selected from one or more of a C1-C15 alkyl group and a C1-C15 alkoxy group.

[0025] Preferably, Ar1 is selected from one of the substituents represented by formula (1) to formula (6):

[0026]

[0027] R3 is selected from H, C1~C20 alkyl or C1~C20 alkoxy;

[0028] And / or, Ar2 is selected from one of the substituents shown in formula (7) to formula (10):

[0029]

[0030] R4 is selected from H, C1~C20 alkyl or C1~C20 alkoxy;

[0031] R5 is selected from H, C1~C10 alkyl or C1~C10 alkoxy.

[0032] Preferably, a1 / (a1+a2) is 80% to 100%.

[0033] Preferably, the conjugated polymer has the structure shown in I-1 or I-2:

[0034] I-1 I-2.

[0035] The present invention also provides a method for preparing the above conjugated polymer, comprising the following steps:

[0036] S1) in a protective atmosphere, a first monomer, a second monomer, a monomer represented by formula (IV) and a monomer represented by formula (V) are subjected to a nucleophilic substitution reaction under a palladium catalyst to obtain an intermediate; the first monomer is selected from a monomer represented by formula (II-1) or a mixture of monomers represented by formula (II-1) and formula (II-2); the second monomer is selected from a monomer represented by formula (III-1) or a mixture of monomers represented by formula (III-1) and formula (III-2);

[0037] S2) reacting the intermediate with a compound represented by formula (VI) to obtain a single-terminated intermediate;

[0038] S3) reacting the single-terminated intermediate with a compound represented by formula (VII) to obtain a conjugated polymer represented by formula (I);

[0039]

[0040]

[0041] X5′-Ar1 formula (VI); H-Ar2 formula (VII);

[0042] X1′ to X5′ are each independently selected from halogen.

[0043] Preferably, the nucleophilic substitution reaction in step S1) is carried out in a solvent; the solvent is selected from one or more of toluene, xylene, dimethyl sulfoxide, N-methylpyrrolidone, N,N-dimethylacetamide and N,N-dimethylformamide;

[0044] And / or, in step S1), a basic compound is further added; the basic compound is selected from one or more of cesium carbonate, sodium carbonate, potassium carbonate, potassium phosphate and triethylamine; the concentration of the basic compound in the reaction system is 0.1-5 mol / L;

[0045] And / or, the palladium catalyst is selected from a divalent palladium catalyst or a zero-valent palladium catalyst;

[0046] and / or, the molar ratio of the palladium catalyst to the first monomer is 1:50 to 1:4000;

[0047] And / or, in step S1), a carboxylic acid is further added; the carboxylic acid is selected from pivalic acid and / or pivalic acid derivatives; the molar ratio of the carboxylic acid to the palladium catalyst is 1:1 to 1:50;

[0048] And / or, the temperature of the nucleophilic substitution reaction in step S1) is 80°C to 130°C; the time of the nucleophilic substitution reaction is 0.5 to 8 h;

[0049] and / or, the molar ratio of the compound represented by formula (VI) to the first monomer is (0.5-5):1;

[0050] And / or, the reaction temperature in step S2) is 80°C to 130°C; the reaction time is 1 to 5 h;

[0051] and / or, the molar ratio of the compound represented by formula (VII) to the first monomer is (0.8-8):1;

[0052] And / or, the reaction temperature in step S3) is 80°C to 130°C; the reaction time is 1 to 5 hours.

[0053] The present invention also provides an application of the conjugated polymer as a black electrochromic material.

[0054] The present invention also provides an electrochromic device, comprising a first transparent electrode layer, an ion storage layer, an electrolyte layer, an electrochromic layer and a second transparent electrode layer arranged in sequence; the electrochromic layer comprises one or more of the above-mentioned conjugated polymers.

[0055] The conjugated polymer provided by the present invention has cyclodioxythiophene as a core functional group and has a chain structure of "donor-bridging group-acceptor", wherein the cyclodioxythiophene derivative as an electron donor has an electron-pushing property, and the nitrogen heterocyclic derivative as an electron acceptor has an electron-withdrawing property, and the charge transfer effect between them has a significant effect on the color change of the material; and a cyclic aromatic hydrocarbon is embedded between the electron donor and the acceptor as a bridging group, and this group does not have an obvious electron-pushing and electron-withdrawing effect, and does not belong to an electron donor or an electron acceptor. Its main function is to adjust the distance between the donor and the acceptor on the polymer chain, thereby optimizing the absorption spectrum of the material and achieving an apparent color closer to pure black; in addition, the presence of the bridging group also expands the chain spacing, promotes the migration of electrolyte ions, effectively reduces the response time and turn-on voltage of the color change process, and significantly improves the cycle life of the material; furthermore, a chemically stable capping group is attached to the chain end to combine with the exposed active site, effectively avoiding the problem of side reactions that are prone to occur in the use of the uncapped material, and improving the chemical stability of the material. In summary, the conjugated polymer provided by the present invention as an electrochromic material not only realizes a black coloring state, but also gives the material a shorter response time, a lower turn-on voltage and a longer cycle life, which is of great significance for the research and development of high-performance electrochromic materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 A schematic diagram of the structure of the electrochromic device provided by the present invention;

[0057] Figure 2 is a gel permeation chromatogram of the conjugated polymer Black-1 obtained in Example 1 of the present invention;

[0058] Figure 3 is the infrared spectrum of the conjugated polymer Black-1 obtained in Example 1 of the present invention;

[0059] Figure 4 The differential scanning calorimetry test and thermogravimetric test result diagram of the conjugated polymer Black-1 obtained in Example 1 of the present invention;

[0060] Figure 5 is a gel permeation chromatogram of the conjugated polymer Black-2 obtained in Example 2 of the present invention;

[0061] Figure 6 is the infrared spectrum of the conjugated polymer Black-2 obtained in Example 2 of the present invention;

[0062] Figure 7 The differential scanning calorimetry test and thermogravimetric test result diagram of the conjugated polymer Black-2 obtained in Example 2 of the present invention;

[0063] Figure 8 The differential scanning calorimetry test and thermogravimetric test result diagram of the conjugated polymer Black-3 obtained in Comparative Example 1 of the present invention;

[0064] Fig. 9 The differential scanning calorimetry test and thermogravimetric test result diagram of the conjugated polymer Black-4 obtained in Comparative Example 2 of the present invention;

[0065] Fig.10 It is a graph showing the test results of UV-visible absorption spectra of Black-1 prepared in Example 1 of the present invention, Black-2 prepared in Example 2, Black-3 prepared in Comparative Example 1, and Black-4 prepared in Comparative Example 2;

[0066] Fig.11 This is a test result diagram of the fading time and coloring time of the solid electrochromic device prepared from the Black-1 material in Example 1 of the present invention;

[0067] Fig.12 This is a test result diagram of the fading time and coloring time of the solid electrochromic device prepared from the Black-2 material in Example 2 of the present invention;

[0068] Fig.13This is a test result diagram of the fading time and coloring time of the solid electrochromic device prepared from the Black-3 material in Example 3 of the present invention;

[0069] Fig.14 This is a test result diagram of the fading time and coloring time of the solid electrochromic device prepared from the Black-4 material in Example 4 of the present invention;

[0070] Fig.15 This is a graph showing the 300-cycle switching test result of the solid electrochromic device made of the Black-1 material in Example 1 of the present invention;

[0071] Fig.16 This is a graph showing the 300-cycle switching test result of the solid electrochromic device made of Black-2 material in Example 2 of the present invention;

[0072] Fig.17 This is a graph showing the 300-cycle switching test result of the solid electrochromic device made of the Black-3 material in Example 3 of the present invention;

[0073] Fig.18 This is a graph showing the 300-cycle switching test result of the solid electrochromic device made of Black-4 material in Example 4 of the present invention. DETAILED DESCRIPTION

[0074] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0075] The present invention provides a conjugated polymer, as shown in formula (I):

[0076] Formula (I);

[0077] Wherein, a1 is an integer of 1 to 15, a2 is an integer of 0 to 5, the sum of a1+a2 is an integer of 1 to 20, b is an integer of 1 to 10, c is an integer of 1 to 5; n is the degree of polymerization;

[0078] R 1-1 ~R 1-8 Each independently represents H, a C1~C10 alkyl group or a C1~C10 alkoxy group;

[0079] R2 is H, C1~C20 alkyl or C1~C20 alkoxy;

[0080] X1 and X2 are H or C-R1′; when X1 and X2 are H, X5 and X6 do not exist; when X1 and X2 are C-R1′, X5 and X6 are each independently C-R2′;

[0081] X3 and X4 are H or C-R3′; when X3 and X4 are H, X7 and X8 are not present; when X3 and X4 are C-R3′, X7 and X8 are each independently C-R4′;

[0082] X9 is selected from S, O or N-R5′;

[0083] X 10 With X 11 is H or C-R6′; when the X 10 With X 11 When H, X 12 With X 13 does not exist; when the X 10 With X 11 When it is C-R6′, X 12 With X 13 Each independently is C-R7′;

[0084] R1′ to R7′ are each independently selected from H, C1 to C10 alkyl or C1 to C10 alkoxy;

[0085] Ar1 is selected from substituted or unsubstituted phenyl, substituted or unsubstituted condensed ring aryl;

[0086] Ar2 is selected from substituted or unsubstituted dibenzazepamycin;

[0087] The substituents in the substituted phenyl group, the substituted condensed ring aromatic group and the substituted dibenzazepine heterocyclic group are each independently selected from one or more of a C1-C20 alkyl group and a C1-C20 alkoxy group.

[0088] In order to achieve the ideal black coloration state of conjugated polymers, the ratio of each monomer unit must be reasonably controlled.

[0089] Wherein, a1 is an integer of 1 to 15, preferably an integer of 5 to 15, more preferably an integer of 10 to 15, and more preferably an integer of 12 to 14. a2 is an integer of 0 to 5, preferably an integer of 0 to 4, and more preferably an integer of 0 to 3. The sum of a1+a2 is an integer of 1 to 20, preferably an integer of 5 to 20, more preferably an integer of 10 to 20, more preferably an integer of 10 to 18, and most preferably an integer of 12 to 17. The a1 / (a1+a2) is preferably 80% to 100%, more preferably 82% to 100%; in some embodiments provided by the present invention, the a1 / (a1+a2) is specifically 14:17 or 1:1.

[0090] b is an integer of 1 to 10, preferably an integer of 3 to 10, more preferably an integer of 5 to 10, further preferably an integer of 5 to 8, further preferably an integer of 6 to 8, and most preferably 7.

[0091] c is an integer of 1-5, preferably an integer of 1-3, and more preferably an integer of 1-2.

[0092] n is the degree of polymerization. By adjusting the value of n, the conjugated polymer can have different molecular weights. Too low molecular weight is not conducive to the film formation of the material, while too high molecular weight will reduce the solubility of the material and is not conducive to the solution processing of the material. Therefore, the preferred value of n in the present invention is that the number average molecular weight Mn of the conjugated polymer is 3000-200000, more preferably 3000-150000, more preferably 3000-100000, more preferably 5000-80000, and most preferably 5000-50000.

[0093] The conjugated polymer provided by the present invention mainly consists of three parts: a donor group (core functional group), a bridging group and an acceptor group, wherein the thiophene derivative monomer unit is an electron donor group, and the nitrogen heterocyclic derivative monomer unit is an electron acceptor group.

[0094] R 1-1 ~R 1-8 Each is independently H, C1~C10 alkyl or C1~C10 alkoxy, preferably H, C1~C6 alkyl or C1~C6 alkoxy, more preferably H, C1~C5 alkyl or C1~C5 alkoxy, and further preferably H, methyl, methoxy, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl or tert-butyl.

[0095] R2 is H, C1~C20 alkyl or C1~C20 alkoxy, preferably H, C1~C15 alkyl or C1~C15 alkoxy, more preferably H, methoxy, methyl, ethoxy, n-propoxy, isopropoxy, n-butoxy, sec-butoxy, tert-butoxy, isopentyloxy, 2-ethylhexyloxy, n-hexyloxy, n-heptyloxy, n-octyloxy, n-nonyloxy, n-decyloxy, n-undecyloxy, n-dodecyloxy, 2-butyloctyloxy, 2-hexyldecyloxy, 2-octyldodecyloxy or 2-decyltetradecyloxy.

[0096] The donor group is one or several cyclodioxythiophene derivatives. The thiophene group will produce an electrochemical reaction under the stimulation of an electrical signal, thereby causing a change in the appearance color. It is the core group that enables the polymer material to realize the electrochromic function. In addition, the present invention modifies the thiophene group into a cyclodioxythiophene with an alkyl chain attached. The presence of the alkyl chain is of vital importance to improving the solubility of polythiophene.

[0097] The bridging group is distributed in the polymer main chain, which can adjust the distance between the donor and the acceptor in the polymer chain, control the charge transfer effect between the donor group and the acceptor group, achieve the ideal light color, and can also expand the distance between the polymer chains, thereby improving the electrochromic response speed. In the present invention, the bridging group is benzene and / or a condensed ring aromatic group, but the larger the conjugated plane, the lower its solubility in the solution. Therefore, the bridging group in the present invention is a group formed by connecting one or more groups of the groups shown in formula (A-1), formula (A-2) and formula (A-3). The site where the bridging group is connected to the main chain will also affect the polymerization reaction activity and color change performance. Therefore, the present invention also clearly describes the connection site of the bridging group. When benzene is used as the bridging group, its 1,4 positions are connected to the polymer main chain. When naphthalene is used as the bridging group, its 1,4 positions are connected to the main chain. When anthracene is used as the bridging group, its 9,10 positions are connected to the main chain.

[0098]

[0099] R1′~R4′ are each independently H, C1~C10 alkyl or C1~C10 alkoxy, preferably H, C1~C6 alkyl or C1~C6 alkoxy, more preferably H, C1~C5 alkyl or C1~C5 alkoxy, and further preferably H, methyl, methoxy, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl or tert-butyl.

[0100] The nitrogen heterocyclic derivative monomer unit is an acceptor group, which is a group represented by formula (A-4) or a group represented by formula (A-5):

[0101]

[0102] X9 is S, O or N-R5′; R5′~R7′ are each independently H, C1~C10 alkyl or C1~C10 alkoxy, preferably H, C1~C6 alkyl or C1~C6 alkoxy, more preferably H, C1~C5 alkyl or C1~C5 alkoxy, and further preferably H, methyl, methoxy, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl or tert-butyl.

[0103] Ar1 and Ar2 are end-capping groups, which are stable groups that do not contain active sites such as active hydrogen atoms or halogen atoms.

[0104] Ar1 is substituted or unsubstituted phenyl, substituted or unsubstituted condensed ring aryl, preferably substituted or unsubstituted phenyl, substituted or unsubstituted naphthyl, substituted or unsubstituted anthracenyl; the substituents in the substituted phenyl and substituted condensed ring aryl are each independently one or more of C1~C20 alkyl and C1~C20 alkoxy, preferably one or more of H, C1~C15 alkyl and C1~C15 alkoxy, more preferably one or more of H, methyl, methoxy, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, isopentyl, 2-ethylhexyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, n-undecyl, n-dodecyl, 2-butyloctyl, 2-hexyldecyl, 2-octyldodecyl and 2-decyltetradecyl.

[0105] In a specific embodiment provided by the present invention, Ar1 is one of the substituents represented by formula (1) to formula (6):

[0106]

[0107] R3 is H, C1~C20 alkyl or C1~C20 alkoxy, preferably H, C1~C15 alkyl or C1~C15 alkoxy, more preferably H, methyl, methoxy, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, isopentyl, 2-ethylhexyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, n-undecyl, n-dodecyl, 2-butyloctyl, 2-hexyldecyl, 2-octyldodecyl or 2-decyltetradecyl.

[0108] Ar2 is a substituted or unsubstituted dibenzazepine heterocyclic group, preferably a substituted or unsubstituted carbazolyl, a substituted or unsubstituted phenoxazinyl, a substituted or unsubstituted phenothiazinyl, or a substituted or unsubstituted acridinyl group; the substituent in the substituted dibenzazepine heterocyclic group is one or more of a C1-C20 alkyl group and a C1-C20 alkoxy group, preferably one or more of a C1-C15 alkyl group and a C1-C15 alkoxy group, more preferably one or more of a H, a methyl group, a methoxy group, an ethyl group, a n-propyl group, an isopropyl group, a n-butyl group, a sec-butyl group, a tert-butyl group, an isopentyl group, a 2-ethylhexyl group, a n-hexyl group, a n-heptyl group, a n-octyl group, a n-nonyl group, a n-decyl group, a n-undecyl group, a n-dodecyl group, a 2-butyloctyl group, a 2-hexyldecyl group, a 2-octyldodecyl group, and a 2-decyltetradecyl group.

[0109] In a specific embodiment provided by the present invention, Ar2 is one of the substituents shown in formula (7) to formula (10):

[0110]

[0111] R4 is H, C1~C20 alkyl or C1~C20 alkoxy, preferably H, C1~C15 alkyl or C1~C15 alkoxy, more preferably H, methyl, methoxy, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, isopentyl, 2-ethylhexyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, n-undecyl, n-dodecyl, 2-butyloctyl, 2-hexyldecyl, 2-octyldodecyl or 2-decyltetradecyl.

[0112] R5 is H, C1~C10 alkyl or C1~C10 alkoxy, preferably H, C1~C6 alkyl or C1~C6 alkoxy, more preferably H, C1~C5 alkyl or C1~C5 alkoxy, and further preferably H, methyl, methoxy, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl or tert-butyl.

[0113] In the present invention, most preferably, the conjugated polymer has the structure shown in I-1 or I-2:

[0114] I-1 I-2

[0115] The present invention also provides a method for preparing the above-mentioned conjugated polymer, comprising the following steps: S1) in a protective atmosphere, a first monomer, a second monomer, a monomer represented by formula (IV) and a monomer represented by formula (V) are subjected to a nucleophilic substitution reaction under the catalysis of a palladium catalyst to obtain an intermediate; the first monomer is selected from a monomer represented by formula (II-1) or a mixture of monomers represented by formula (II-1) and formula (II-2); the second monomer is selected from a monomer represented by formula (III-1) or a mixture of monomers represented by formula (III-1) and formula (III-2); S2) the intermediate is reacted with a compound represented by formula (VII) to obtain a single-terminated intermediate; S3) the single-terminated intermediate is reacted with a compound represented by formula (VIII) to obtain a conjugated polymer represented by formula (I);

[0116]

[0117]

[0118] X5′-Ar1 formula (VI); H-Ar2 formula (VII);

[0119] X1′ to X4′ are each independently halogen.

[0120] The present invention has no special restrictions on the sources of all raw materials, and any raw materials available on the market can be used; 1-1 ~R 1-8 , R2, X1~X 11, Ar1 and Ar2 are the same as described above and will not be repeated here; and X1′~X4′ are each independently preferably Br or Cl.

[0121] In a specific embodiment provided by the present invention, the compound represented by formula (VI) is specifically one of the structures shown below:

[0122]

[0123] In a specific embodiment provided by the present invention, the compound represented by formula (VII) is specifically one of the structures shown below:

[0124]

[0125] R6 is H, C1~C20 alkyl or C1~C20 alkoxy, preferably H, C1~C15 alkyl or C1~C15 alkoxy, more preferably H, methyl, methoxy, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, isopentyl, 2-ethylhexyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, n-undecyl, n-dodecyl, 2-butyloctyl, 2-hexyldecyl, 2-octyldodecyl or 2-decyltetradecyl.

[0126] In a protective atmosphere, a first monomer, a second monomer, a monomer represented by formula (IV) and a monomer represented by formula (V) are subjected to a nucleophilic substitution reaction under the catalysis of a palladium catalyst to obtain an intermediate; the protective atmosphere can be a protective atmosphere well known to those skilled in the art and is not particularly limited. In the present invention, nitrogen is preferably used; the sum of the moles of the second monomer, the monomer represented by formula (IV) and the monomer represented by formula (V) is preferably equal to the mole number of the first monomer; more specifically, the molar ratio of the first monomer, the second monomer, the monomer represented by formula (IV) and the monomer represented by formula (V) is 7±2:2±1:2±1:1; the nucleophilic substitution reaction is preferably carried out in a solvent; the solvent is preferably an organic solvent with a relatively high boiling point. The organic solvent is preferably one or more of toluene, xylene, dimethyl sulfoxide, N-methylpyrrolidone, N,N-dimethylacetamide and N,N-dimethylformamide; since the nucleophilic substitution reaction needs to be carried out under anhydrous and oxygen-free conditions, the solvent is preferably dried with a molecular sieve for more than 12 hours before use; the nucleophilic substitution reaction needs to be carried out smoothly under alkaline conditions, so this step preferably also adds an alkaline compound; the alkaline compound is an alkaline compound well known to those skilled in the art, and there is no special limitation. In the present invention, it is preferably one or more of cesium carbonate, sodium carbonate, potassium carbonate, potassium phosphate and triethylamine; the concentration of the alkaline compound in the reaction system is preferably 0.1~5 The molar ratio of the carboxylic acid to the palladium catalyst is preferably 1:1-1:50, more preferably 1:1-1:30, and more preferably 1:5-1:20; the palladium catalyst is preferably a divalent palladium catalyst or a zero-valent palladium catalyst, and more preferably palladium acetate; the molar ratio of the palladium catalyst to the monomer represented by formula (III) is preferably 1:50-1:4000, more preferably 1:50-1:1000, more preferably 1:50-1:500, and most preferably 1:50-1:300; the temperature of the nucleophilic substitution reaction is preferably 80°C-130°C, and more preferably 85°C-120°C; the time of the nucleophilic substitution reaction is preferably 0.5-8 h, more preferably 1-5 h, and more preferably 1-3 h.

[0127] In a specific embodiment provided by the present invention, the step S1) is specifically: mixing the first monomer, the second monomer, the monomer represented by formula (IV), the monomer represented by formula (V), the solvent and the alkaline compound, replacing the air in the reaction system with a protective atmosphere, then adding a palladium catalyst and a carboxylic acid, and then performing gas replacement to remove water and oxygen in the reaction system, heating to perform a nucleophilic substitution reaction, and obtaining an intermediate.

[0128] The intermediate polymer chain ends obtained by the nucleophilic substitution reaction will have exposed hydrogen atoms and bromine atoms. These sites have high electrochemical and photochemical activities and will produce more side reactions during the electrochromic process. Therefore, the present invention further introduces monofunctional capping groups to react with hydrogen atoms and bromine atoms to avoid the negative impact of active sites on cyclic stability.

[0129] The intermediate is reacted with a compound represented by formula (VI) to obtain a single-terminated intermediate; the molar ratio of the compound represented by formula (VI) to the first monomer is preferably (0.5-5):1; the reaction temperature is preferably 80°C-130°C, more preferably 85°C-120°C; the reaction time is preferably 1-5 h, more preferably 1-4 h, and more preferably 2-3 h.

[0130] The single-terminated intermediate is reacted with a compound represented by formula (VII); the molar ratio of the compound represented by formula (VII) to the first monomer is preferably (0.8-8):1; the reaction temperature is preferably 80°C-130°C, more preferably 85°C-120°C; the reaction time is preferably 1-5 h, more preferably 1-4 h, and more preferably 2-3 h.

[0131] After the reaction is completed, the reaction solution is preferably mixed with an alcohol-water mixed solution and filtered to obtain a crude product; the crude product is recrystallized, pulped, filtered, and crushed, and then Soxhlet extracted with ethanol, acetone, n-hexane and dichloromethane in sequence, and the dichloromethane extract is added to ethanol for precipitation to obtain a conjugated polymer represented by formula (I); the alcohol-water mixed solution is preferably an ethanol-water mixed solution; the volume ratio of the alcohol solvent to water in the alcohol-water mixed solution is preferably (3~5):1, more preferably 4:1; the good solvent for recrystallization is preferably chloroform; the poor solvent for recrystallization is preferably an alcohol solvent, more preferably ethanol; the number of recrystallizations is preferably 1~4 times, more preferably 2~3 times; the pulping treatment is preferably carried out using deionized water and ethanol respectively; the number of pulping treatments using deionized water is preferably 2~3 times; the number of pulping treatments using ethanol is preferably 2~3 times; inorganic salts and unreacted raw materials can be washed away by pulping.

[0132] The present invention also provides an application of the conjugated polymer as a black electrochromic material.

[0133] To be more specific, the conjugated polymer has electrochromic properties and can be used in applications such as color-changing glass / screen display / electric energy storage / intelligent response, and the multifunctional application of the material can also be achieved by integrating the above functions, for example, capacitors with intelligent color-changing response, sensors with electrically controlled fluorescence properties, and photoelectric electrochromic devices.

[0134] The present invention also provides an electrochromic device, comprising a first transparent electrode layer, an ion storage layer, an electrolyte layer, an electrochromic layer and a second transparent electrode layer arranged in sequence; the electrochromic layer comprises one or more of the above-mentioned conjugated polymers.

[0135] See also Figure 1 , Figure 1 This is a schematic structural diagram of the electrochromic device provided by the present invention.

[0136] In a specific embodiment provided by the present invention, the ion storage layer is vanadium pentoxide; the thickness of the ion storage layer is preferably 10-50 μm, more preferably 20-40 μm, and even more preferably 30 μm.

[0137] In a specific embodiment provided by the present invention, the electrolyte layer comprises propylene carbonate, lithium trifluoromethanesulfonate, polyethylene glycol acrylate and benzoin dimethyl ether; the mass of the propylene carbonate is 10% to 40% of the mass of the electrolyte layer; the mass of the lithium trifluoromethanesulfonate is 5% to 20% of the mass of the electrolyte layer; the mass of the polyethylene glycol acrylate is 10% to 50% of the mass of the electrolyte layer; the mass of the benzoin dimethyl ether is 5% to 10% of the mass of the electrolyte layer; the thickness of the electrolyte layer is preferably 100 to 500 μm, more preferably 200 to 400 μm, and even more preferably 200 to 300 μm.

[0138] In the present invention, the electrochromic device can be prepared according to methods well known to those skilled in the art, wherein the electrochromic layer is preferably prepared by a scraping coating process which is more conducive to large-area preparation, specifically: one or more of the conjugated polymers shown in formula (I) are dissolved to obtain a slurry, and then the slurry is scraped to form a film. The solvent used for the dissolution should be a solvent or a mixed solvent of several solvents that have a high solubility for the conjugated polymer, including but not limited to n-hexane, dichloromethane, chloroform, tetrahydrofuran, toluene, xylene and other solvents; the concentration of the conjugated polymer in the slurry is preferably 5-80 mg / mL, more preferably 15-50 mg / mL; the scraping coating is preferably carried out on an automatic coating machine to eliminate the negative impact that manual operation may have on the film quality. During the processing, the thickness of the electrochromic film should be strictly controlled in the range of 5 μm to 5000 μm, preferably, the thickness of the electrochromic film is 8 μm to 300 μm, and the scraper movement speed should be regulated between 0.5 cm / s and 300 cm / s, preferably, the movement speed is between 2.5 cm / s and 100 cm / s.

[0139] The innovation of the present invention is mainly reflected in the following aspects: First, the "donor-bridging group-acceptor" type polymer structure is adopted, so that the material exhibits an apparent color closer to pure black; second, through the introduction of the bridging group, the chain spacing of the polymer is effectively expanded, which facilitates the rapid entry and exit of electrolyte ions, thereby significantly improving the response speed of the material; finally, the present invention cleverly adds a capping group, successfully solving the problem that the active sites at the chain ends of the original material are prone to side reactions, thereby extending the cycle life of the material. In summary, the present invention not only solves the problem of the lack of pure black color materials in existing electrochromic products, but also improves its shortcomings such as long response time and low cycle life, laying a solid foundation for the commercial application of pure black electrochromic devices.

[0140] In order to further illustrate the present invention, a conjugated polymer provided by the present invention, a preparation method thereof and an application in an electrochromic device are described in detail below in conjunction with examples.

[0141] The reagents used in the following examples are all commercially available.

[0142] Example 1

[0143] The chemical structure of the polymer Black-1 prepared in this example is shown in I-1, and the specific synthesis steps are as follows:

[0144] I-1

[0145]

[0146] Cyclodioxythiophene derivatives B-1 (6 mmol, 2.64 g), B-2 (1 mmol, 0.60 g), B-3 (1.5 mmol, 0.45 g), aromatic ring compounds B-4 (3 mmol, 0.71 g), nitrogen heterocyclic receptor compounds B-5 (0.5 mmol, 0.15 g), potassium carbonate (50 mmol, 6.90 g) and solvent N,N-dimethylformamide (50 mL) were added to the flask, and then the air in the system was replaced with dry nitrogen using a Shrek tube. Catalysts palladium acetate (0.8 mmol, 0.18 g) and pivalic acid (8 mmol, 0.82 g) were then added to the flask, and gas replacement was performed again to ensure that water and oxygen inside the flask were removed. Turn on the stirrer, stir for 10 minutes, raise the temperature to 110°C, react for 2 hours, add compound B-6 (12 mmol, 1.88 g) and continue to react for 2 hours, then add compound B-7 (20 mmol, 5.58 g) and continue to react for 2 hours. After the reaction is completed, turn off the heating, transfer the solution to a mixed solution of 400 mL ethanol and 100 mL deionized water, let it stand and filter to obtain a black crude product. The crude product is then recrystallized three times using chloroform as a good solvent and ethanol as a poor solvent, and then slurried three times with deionized water and ethanol to wash away inorganic salts and unreacted raw materials. The solid was then crushed with a grinder to obtain a black powder, which was subjected to Soxhlet extraction with ethanol, acetone, n-hexane and dichloromethane in sequence. The product in dichloromethane was dropped into ethanol for precipitation, filtered and dried to obtain 2.7 g of the final product I-1, a conjugated polymer Black-1 (Mn = 13582 g / mol, PDI = 1.33), which has good thermal stability (glass transition temperature T g The thermal weight loss temperature is 154℃. d is 483℃).

[0147] The conjugated polymer Black-1 obtained in Example 1 was analyzed by gel permeation chromatography, and its gel permeation chromatogram was obtained as shown in FIG. Figure 2 shown.

[0148] The conjugated polymer Black-1 shown in I-1 obtained in Example 1 was analyzed by infrared spectrometer, and the infrared spectrum was obtained as shown in FIG. Figure 3 As shown, the results of FTIR (cm -1): 2954.64, 2927.74, 2854.65, 1485.64,1464.01, 1432.17, 1366.96, 1298.83, 1187.76, 1100.20, 1048.23, 891.42,832.11, 764.30, 727.95, 651.11, 616.46, 547.73, 525.59, 510.25. Among them, 2954.64cm -1 , 2927.74 cm -1 , 2854.65 cm -1 Assigned to stretching vibration of CH bond, 1485.64 cm -1 , 1464.01 cm -1 , 1432.17 cm -1 , 1366.96 cm -1 Vibration attributed to the thiophene group, benzene ring, and benzothiadiazole skeleton, 1100.20 cm -1 , 1048.23 cm -1 It is attributed to the C—C stretching vibration between the thiophene group and the substituent.

[0149] The Black-1 material was subjected to differential scanning calorimetry and thermal gravimetric test, and the results of the differential scanning calorimetry and thermal gravimetric test were shown in the figure below. Figure 4 As shown. Figure 4 It can be seen that its glass transition temperature T g The thermal decomposition temperature (the temperature at which 5% mass loss occurs) is 483°C.

[0150] Example 2

[0151] The chemical structure of the polymer Black-2 prepared in this example is shown in I-2, and the specific synthesis steps are as follows:

[0152] I-2

[0153]

[0154] Cyclodioxythiophene derivative formula B-1 (5 mmol, 2.20 g), formula B-2 (1 mmol, 0.60 g), aromatic ring compound formula B-8 (3 mmol, 0.86 g), nitrogen heterocyclic acceptor compound formula B-9 (0.5 mmol, 0.25 g), potassium carbonate (45 mmol, 6.21 g) and solvent N,N-dimethylformamide (45 mL) were added to the flask, and then the air in the system was replaced with dry nitrogen using a Shrek tube. Catalyst palladium acetate (0.7 mmol, 0.16 g) and pivalic acid (7 mmol, 0.72 g) were then added to the flask, and gas replacement was performed again to ensure that water and oxygen inside the flask were removed. Turn on the stirrer, stir for 10 minutes, raise the temperature to 110 ° C, react for 2 hours, add compound B-10 (10 mmol, 2.13 g) and continue to react for 2 hours, then add compound B-11 (15 mmol, 2.51 g) and continue to react for 2 hours. After the reaction is completed, turn off the heating, transfer the solution to a mixed solution of 400 mL ethanol and 100 mL deionized water, let it stand and filter to obtain a black crude product. The crude product is then recrystallized three times using chloroform as a good solvent and ethanol as a poor solvent, and then slurried three times with deionized water and ethanol to wash away inorganic salts and unreacted raw materials. The solid was then crushed with a grinder to obtain a black powder, which was subjected to Soxhlet extraction with ethanol, acetone, n-hexane and dichloromethane in sequence. The product in dichloromethane was dropped into ethanol for precipitation, filtered and dried to obtain 2.33 g of the final product I-2, a conjugated polymer Black-2 (Mn = 12561 g / mol, PDI = 1.42), which has good thermal stability (glass transition temperature T g The thermal weight loss temperature is 161℃. d is 506℃).

[0155] The conjugated polymer Black-2 obtained in Example 2 was analyzed by gel permeation chromatography, and its gel permeation chromatogram was obtained as shown in FIG. Figure 5 shown.

[0156] The conjugated polymer Black-2 shown in I-2 obtained in Example 2 was analyzed by infrared spectrometer, and its infrared spectrum was obtained as shown in FIG. Figure 6 As shown, the results of FTIR (cm -1): 2954.42, 2920.04, 2854.60, 1465.29,1430.89, 1364.25, 1297.97, 1187.42, 1156.90, 1099.37, 1047.21, 887.28,831.39, 763.62, 725.46, 670.35, 644.11, 616.47, 568.42, 548.22, 531.52,524.84, 515.13, 502.41. Among them, 2954.42 cm -1 , 2920.04 cm -1 , 2854.60 cm -1 Assigned to stretching vibration of CH bond, 1465.29 cm -1 , 1430.89 cm -1 , 1364.25 cm -1 , 1297.97 cm -1 Vibration attributed to the thiophene group, naphthalene ring and benzothiadiazole skeleton, 1099.37 cm -1 , 1047.21 cm -1 It is attributed to the C—C stretching vibration between the thiophene group and the substituent.

[0157] The Black-2 material was subjected to differential scanning calorimetry and thermal gravimetric test, and the results of the differential scanning calorimetry and thermal gravimetric test were shown in the figure below. Figure 7 As shown. Figure 7 It can be seen that its glass transition temperature T g The thermal decomposition temperature is 161°C and 506°C.

[0158] Comparative Example 1

[0159] The chemical structure of polymer Black-3 is shown in Formula C. The material does not introduce an aromatic ring bridging group and is not end-capped. The specific synthesis steps are as follows:

[0160] Formula C

[0161] Add cyclodioxythiophene derivatives B-1 (4 mmol, 1.76 g), B-2 (3 mmol, 1.79 g), nitrogen heterocyclic receptor compound B-5 (1 mmol, 0.29 g), potassium carbonate (35 mmol, 4.83 g) and solvent N,N-dimethylformamide (35 mL) to the flask, and then use a Shrek tube to replace the air in the system with dry nitrogen. Then add the catalyst palladium acetate (0.5 mmol, 0.11 g) and pivalic acid (5 mmol, 0.51 g) to the flask, and perform gas replacement again to ensure that the water and oxygen inside the flask are removed. Turn on the stirrer, stir for 10 minutes, raise the temperature to 110°C, react for 2 hours, turn off the heating, transfer the solution to a mixed solution of 400 mL ethanol and 100 mL deionized water, let it stand and filter, and obtain a black crude product. The crude product was then recrystallized three times using chloroform as a good solvent and ethanol as a poor solvent, and then slurried three times with deionized water and ethanol to wash away inorganic salts and unreacted raw materials. The solid was then crushed with a grinder to obtain a black powder, which was then Soxhlet extracted with ethanol, acetone, n-hexane and dichloromethane in turn. The product in dichloromethane was dropped into ethanol for sedimentation, filtered and dried to obtain 1.89 g of the final product Black-3 (Mn = 12701 g / mol, PDI = 1.36), which has good thermal stability (glass transition temperature T g The thermal weight loss temperature is 140℃. d is 462℃).

[0162] The Black-3 material was subjected to differential scanning calorimetry and thermal gravimetric test, and the results of the differential scanning calorimetry and thermal gravimetric test were shown in the figure below. Figure 8 shown.

[0163] Comparative Example 2

[0164] The chemical structure of polymer Black-4 is shown in Formula D. The material is not end-capped. The specific synthesis steps are as follows:

[0165] Formula D

[0166] Add cyclodioxythiophene derivatives B-1 (4 mmol, 1.76 g), B-2 (1 mmol, 0.60 g), aromatic ring compound B-4 (2 mmol, 0.47 g), nitrogen heterocyclic acceptor compound B-5 (1 mmol, 0.29 g), potassium carbonate (35 mmol, 4.83 g) and solvent N,N-dimethylformamide (35 mL) to the flask, and then use a Shrek tube to replace the air in the system with dry nitrogen. Then add catalyst palladium acetate (0.5 mmol, 0.11 g) and pivalic acid (5 mmol, 0.51 g) to the flask, and perform gas replacement again to ensure that the water and oxygen inside the flask are removed. Turn on the stirrer, stir for 10 minutes, raise the temperature to 110 ° C, react for 2 hours, turn off the heating, transfer the solution to a mixed solution of 400 mL ethanol and 100 mL deionized water, let it stand and filter, and obtain a black crude product. The crude product was then recrystallized three times using chloroform as a good solvent and ethanol as a poor solvent, and then slurried three times with deionized water and ethanol to wash away inorganic salts and unreacted raw materials. The solid was then crushed with a grinder to obtain a black powder, which was then Soxhlet extracted with ethanol, acetone, n-hexane and dichloromethane in turn. The product in dichloromethane was dropped into ethanol for sedimentation, filtered and dried to obtain 1.58 g of the final product Black-4 (Mn = 14684 g / mol, PDI = 1.41), which has good thermal stability (glass transition temperature T g The thermal weight loss temperature is 170℃. d is 431℃).

[0167] The Black-4 material was subjected to differential scanning calorimetry and thermal gravimetric test, and the results of the differential scanning calorimetry and thermal gravimetric test were shown in the figure below. Fig. 9 shown.

[0168] Example 3

[0169] The solubility of the above materials was tested. The four materials have solubility in several common organic solvents as shown in Table 1, and they have the best solubility in tetrahydrofuran, toluene, xylene and dichloromethane.

[0170] Table 1 Material solubility test results

[0171]

[0172] Note: The concentration of the test solution is 10 mg / ml, where - means completely insoluble, +- means partially soluble under heating conditions, and ++ means soluble at room temperature.

[0173] Example 4

[0174] According to the test results of the solubility of the material, tetrahydrofuran is selected as the solvent in the present invention. The above-prepared material is dissolved in tetrahydrofuran to prepare 10 mL of solution (concentration is 15 mg / mL), and then a 50 μm slit is selected by an automatic coating machine, and a film is scraped on the conductive surface of PET-ITO at a speed of 10 cm / s. After drying, the electrochromic layer is 20 μm. According to the UV-visible absorption spectrum test results of the film, as shown in FIG. Fig.10 As shown, it can be found that the three materials Black-1 described in Example 1, Black-2 described in Example 2 and Black-4 described in the comparative example show relatively uniform wide-range absorption, while in comparison, the absorption spectrum of Black-3 described in the comparative example 1 shows a narrower single-peak absorption, which indicates that the "donor-bridging group-acceptor" structure of Black-1, Black-2 and Black-4 materials successfully plays the role of broadening the absorption spectrum and achieving a purer black.

[0175] Example 5

[0176] according to Figure 1 The structure shown in the figure is used to assemble the electrochromic material with the electrolyte material, the ion storage layer material and the transparent electrode material into a solid electrochromic device. The electrolyte layer is composed of propylene carbonate (8 g), lithium trifluoromethanesulfonate (1.5 g), polyethylene glycol acrylate (40 g) and benzoin dimethyl ether (2.5 g), with a thickness of 200 μm; the ion storage layer is vanadium pentoxide, with a thickness of 30 μm; the transparent electrode layer is a PET-ITO conductive film, with a PET thickness of 100 μm and an ITO thickness of 30 μm. The electrochromic layer is scraped according to the conditions described in Example 4, and the dry film thickness is 8 μm. The response time and cycle stability of the electrochromic devices of each material are tested by combining an electrochemical workstation and a UV-visible absorption spectrometer, and the results are shown in Table 2; the test results of the fading time and coloring time of the solid electrochromic device prepared with the Black-1 material are shown in Figure 2. Fig.11 As shown; the test results of fading time and coloring time of the solid electrochromic device prepared by Black-2 material are shown in FIG. Fig.12 As shown; the test results of fading time and coloring time of the solid electrochromic device prepared by Black-3 material are shown in FIG. Fig.13 As shown; the test results of fading time and coloring time of the solid electrochromic device prepared by Black-4 material are shown in FIG. Fig.14 As shown; the 300-cycle switching cycle test results of the solid electrochromic device prepared by Black-1 material are shown in FIG. Fig.15 As shown; the 300-cycle switching cycle test results of the solid electrochromic device prepared by Black-2 material are shown in FIG. Fig.16As shown; the 300-cycle switching cycle test results of the solid electrochromic device prepared by Black-3 material are shown in FIG. Fig.17 As shown; the 300-cycle switching cycle test results of the solid electrochromic device prepared by Black-4 material are shown in FIG. Fig.18 shown.

[0177] Table 2 Test results of solid electrochromic layer devices

[0178]

[0179] Note: ΔT is the difference between the transmittance in the colored state and the transmittance in the faded state, and the test wavelength is the wavelength of maximum absorption in the colored state; fading time / coloring time is the time taken for the material to reach 90% of ΔT after being electrically stimulated.

[0180] It can be seen from Table 2 that Black-1, Black-2 and Black-3 of the "donor-bridging group-acceptor" structure have a faster response speed than Black-4. The capping groups of Black-1 and Black-2 make them have a much higher cycle stability than Black-3 and Black-4.

[0181] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A conjugated polymer, characterized in that As shown in formula (I): wherein a1 is an integer of 1 to 15, a2 is an integer of 0 to 5, the sum of a1+a2 is an integer of 10 to 20, b is an integer of 5 to 10, and c is an integer of 1 to 2; and a1 / (a1+a2) is 80% to 100%; n is the degree of polymerization; the number average molecular weight Mn of the conjugated polymer is 3000 to 200000; R 1-1 ~R 1-8 are each independently selected from H; R2 is selected from H, C1-C20 alkyl or C1-C20 alkoxy; X1 and X2 are both H or both C-R1′; when X1 and X2 are both H, X5 and X6 do not exist; when X1 and X2 are both C-R1′, X5 and X6 are selected from C-R2′; X3 and X4 are both H or C-R3′; when X3 and X4 are both H, X7 and X8 do not exist; when X3 and X4 are both C-R3′, X7 and X8 are selected from C-R4′; X9 is selected from S, O or N-R5′; X 10 With X 11 are H or C-R6′; when the X 10 With X 11 When both are H, X 12 With X 13 does not exist; when the X 10 With X 11 When both are C-R6′, X 12 With X 13 Selected from C-R7′; R1′ to R7′ are each independently selected from H; The Ar1 is selected from one of the substituents represented by formula (1) to formula (6): R3 is selected from H, C1-C15 alkyl or C1-C15 alkoxy; The Ar2 is selected from one of the substituents shown in formula (7) to formula (10): R4 is selected from H, C1-C15 alkyl or C1-C15 alkoxy; R5 is selected from H, C1-C5 alkyl or C1-C5 alkoxy.

2. The conjugated polymer according to claim 1, characterized in that R2 is selected from H, methoxy, methyl, ethoxy, n-propoxy, isopropoxy, n-butoxy, sec-butoxy, tert-butoxy, isopentyloxy, 2-ethylhexyloxy, n-hexyloxy, n-heptyloxy, n-octyloxy, n-nonyloxy, n-decyloxy, n-undecyloxy, n-dodecyloxy, 2-butyloctyloxy, 2-hexyldecyloxy, 2-octyldodecyloxy or 2-decyltetradecyloxy; R3 is selected from H, C1-C15 alkyl or C1-C15 alkoxy; R4 is selected from H, C1-C15 alkyl or C1-C15 alkoxy; R5 is selected from H, C1-C5 alkyl or C1-C5 alkoxy.

3. The conjugated polymer according to claim 1, characterized in that The conjugated polymer has the structure shown in I-1 or I-2:

4. A method for preparing a conjugated polymer according to claim 1, characterized in that: The following steps are involved: S1) in a protective atmosphere, a first monomer, a second monomer, a monomer represented by formula (IV) and a monomer represented by formula (V) are subjected to a nucleophilic substitution reaction under a palladium catalyst to obtain an intermediate; the first monomer is selected from a monomer represented by formula (II-1) or a mixture of monomers represented by formula (II-1) and formula (II-2); the second monomer is selected from a monomer represented by formula (III-1) or a mixture of monomers represented by formula (III-1) and formula (III-2); S2) reacting the intermediate with a compound represented by formula (VI) to obtain a single-terminated intermediate; S3) reacting the single-terminated intermediate with a compound represented by formula (VII) to obtain a conjugated polymer represented by formula (I); X5′-Ar1 formula (VI); H-Ar2 formula (VII); X1' to X5' are each independently selected from halogen.

5. The preparation method according to claim 4, characterized in that: The nucleophilic substitution reaction in step S1) is carried out in a solvent; the solvent is selected from one or more of toluene, xylene, dimethyl sulfoxide, N-methylpyrrolidone, N,N-dimethylacetamide and N,N-dimethylformamide; And / or, in step S1), a basic compound is further added; the basic compound is selected from one or more of cesium carbonate, sodium carbonate, potassium carbonate, potassium phosphate and triethylamine; the concentration of the basic compound in the reaction system is 0.1-5 mol / L; And / or, the palladium catalyst is selected from a divalent palladium catalyst or a zero-valent palladium catalyst; and / or, the molar ratio of the palladium catalyst to the first monomer is 1:50 to 1:4000; And / or, in step S1), a carboxylic acid is further added; the carboxylic acid is selected from pivalic acid and / or pivalic acid derivatives; the molar ratio of the carboxylic acid to the palladium catalyst is 1:1 to 1:50; And / or, the temperature of the nucleophilic substitution reaction in step S1) is 80°C to 130°C; the time of the nucleophilic substitution reaction is 0.5 to 8 hours; and / or, the molar ratio of the compound represented by formula (VI) to the first monomer is (0.5-5):1; And / or, the reaction temperature in step S2) is 80°C to 130°C; the reaction time is 1 to 5 hours; and / or, the molar ratio of the compound represented by formula (VII) to the first monomer is (0.8-8):1; And / or, the reaction temperature in step S3) is 80° C. to 130° C.; the reaction time is 1 to 5 hours.

6. Use of the conjugated polymer according to any one of claims 1 to 3 or the conjugated polymer prepared by the preparation method according to any one of claims 4 to 5 as a black electrochromic material.

7. An electrochromic device, characterized in that: It comprises a first transparent electrode layer, an ion storage layer, an electrolyte layer, an electrochromic layer and a second transparent electrode layer arranged in sequence; the electrochromic layer comprises one or more of the conjugated polymers described in any one of claims 1 to 3 or the conjugated polymers prepared by any one of the preparation methods described in claims 4 to 5.

Citation Information

Patent Citations

  • Electrochromic polymer and synthesis and uses thereof

    CN110892001A